Bioarchaeology of the medieval Đakovo cemetery : Archaeological and anthropological evidence for ethnic affiliation and migration - Šlaus, Mario (Array, 1998)
The results of a multidisciplinary bioarchaeological analysis of the medieval cemetery from Đakovo show that this site was, from the 11th to the 13th century inhabited by the Bijelo Brdo population, and from the 13th to the 16th century, by the populaton of an unknown identity.The demografic profiles of the two burial phases reflect a similar lifestyle and probably a continuance of exploitation of the same resources.